2017
DOI: 10.3389/fnhum.2017.00177
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation Improves the Symptoms and Sensory Signs of Persistent Central Neuropathic Pain from Spinal Cord Injury: A Case Report

Abstract: Central neuropathic pain (CNP) is a significant problem after spinal cord injury (SCI). Pharmacological and non-pharmacological approaches may reduce the severity, but relief is rarely substantial. While deep brain stimulation (DBS) has been used to treat various chronic pain types, the technique has rarely been used to attenuate CNP after SCI. Here we present the case of a 54-year-old female with incomplete paraplegia who had severe CNP in the lower limbs and buttock areas since her injury 30 years prior. She… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“… 35 Direct stimulation of the PAG has successfully been trialled as a treatment option for NP including pain following SCI. 36 Thus, it is anticipated that molecular changes in the PAG could compromise descending inhibition of nociceptive processing and subsequently increase the spinal gain of incoming information. Our study is the first to provide evidence for NP-related changes in PAG microstructure in humans, underscoring the clinical relevance of these changes for NP following SCI.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Direct stimulation of the PAG has successfully been trialled as a treatment option for NP including pain following SCI. 36 Thus, it is anticipated that molecular changes in the PAG could compromise descending inhibition of nociceptive processing and subsequently increase the spinal gain of incoming information. Our study is the first to provide evidence for NP-related changes in PAG microstructure in humans, underscoring the clinical relevance of these changes for NP following SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that NE and M-EK have analgesic effects. Injection of NE and/or opioid agonists into the spinal dorsal horn can achieve analgesic effects ( 25 , 26 ). Microencapsulated PC12 cells can be transplanted into the subarachnoid space of rats, and as a source of microcellular pump, can continuously produce NE and M-EK, and may have a notable analgesic effect in a chronic neurogenic animal model ( 23 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Raphe neurons also secrete several neuropeptides, including galanin, substance P, and thyrotropin-release hormone, that are potentially protective after SCI [32,33]. The relation of NRM LFS to other stimulation targets used for the management of neurotrauma (vagal nerve, periaqueductal grey, spinal cord), for which the modulation of autonomic function is a commonly proposed mechanism, is unclear [6,8,14,16,17,19,35]. However, given the established reciprocal connections between these targets, it is likely that diverse overlapping processes are elicited with each stimulation target [14,26,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, since some degree of functional improvement occurs naturally in the weeks following injury, it is possible that the sequelae of SCI may be overcome to some extent by interventions that enhance endogenous beneficial processes [2,6,7]. Chronic low-frequency electrical stimulation (LFS) of various brain and spinal targets has long been known to influence the perception of chronic pain in select patients [8,9,10]. However, more recently, LFS of several of these targets and their inputs has received attention for its ability to improve functional outcomes in laboratory and clinical models of SCI [6,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%